Enzyme technology : (Noyes Data Corp., 1983)
Enzymesmay be defined as catalytically active proteins, some enzymes consist only of protein; others are complex and have a protein compoment and a cofactor. These cofactors may be metals such as iron or copper, certain organic molecules known as prosthetic groups, or coenzymes.